School Administrator Skills in the 21st Century Affecting the Professional Learning Community in Schools Under the Secondary Educational Service Area Office Chonburi Rayong - Petchpattharangkun, Pakpoom; Mrazek, Punniththa; Ngamkanok, Sumeth (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aims to : 1. study the 21st- century school administrator skills that influence the development of professional learning communities in schools under the Secondary Educational Service Area Office of Chonburi and Rayong, 2. develop a structural equation model of 21st-century school administrator skills affecting the establishment of professional learning communities in schools under the aforementioned office, and 3. validate the consistency of the proposed structural equation model. The sample consisted of 353 school administrators and educational personnel, selected through stratified random sampling based on school size in each province. The study examined five latent variables: communication, teamwork, decision-making, interpersonal relationships, and the development of professional learning communities. The data collected using a questionnaire with reliability coefficients ranging from 0.919 to 0.960. and analyzed through basic statistical analysis, Pearson’s correlation coefficient, and structural equation modeling (SEM). The findings revealed that: 1. the overall leadership skills of school administrators in the 21st century were at a high level, with the highest performing components being decision-making, teamwork, and communication, respectively. 2. the structural equation model indicated that communication significantly influenced the establishment of learning communities at the 0.05 level, while interpersonal relationships and decision-making showed significant influence at the 0.01 level. However, teamwork was not statistically significant. The component weights ranged from 0.72 to 1.01. 3. the goodness-of-fit test showed that the model was consistent with the empirical data, with X2 = 63.933, degrees of freedom = 47, p = 0.051, GFI = 0.973, CFI = 0.992, TLI = 0.988, and RMSEA = 0.032.